Analysis of Foundation Modification with Enlarged Base for Eight-Story Oncology Building at RSUD Haji Surabaya: Analisis Modifikasi Fondasi dengan Pembesaran Ujung pada Bangunan Gedung Onkologi 8 Lantai Rsud Haji Surabaya - Salsabila Aulia; Arasi Arahman; Solin Dian Purnamawati (Universitas 17 Agustus 1945 Surabaya, 2026)
The projected rise in cancer cases in Indonesia, expected to exceed 70% by 2050, underscores the need for accelerated development of healthcare infrastructure, including the Oncology Building at RSUD Haji Surabaya. The presence of soft clay soil at the site requires a foundation system capable of maintaining structural stability and limiting settlement. This study examines the performance of pile group foundations within a raft system through numerical analysis using the Luciano Decourt and Converse–Labarre methods, supported by Allpile simulations, under two design scenarios: an existing foundation without base enlargement and a modified design featuring pile base enlargement.The numerical evaluation shows that the existing configuration provides allowable capacities of 213.91 ton for a single pile and 12,025.79 ton for the pile group, with settlements of 5.22 cm and 11.48 cm. After base enlargement, allowable capacities increase to 330.63 ton and 18,588.17 ton, accompanied by reduced settlements of 1.37 cm and 6.07 cm. Allpile simulations similarly show improved performance, from 17,345.78 ton to 24,731.68 ton after modification.These findings confirm that pile base enlargement significantly enhances bearing capacity and effectively controls settlement, making it a suitable solution for structures on low-strength clay deposits.